KEBUTUHAN FREKUENSI PENERBANGAN RUTE JAKARTA – JOGYAKARTA – JAKARTA PT INDONESIA AIR ASIA - MB Tampubolon; Eddy Suhaedi; Robby Ariyanto (Institut Transportasi dan Logistik Trisakti, 2016)
PT. Indonesia Air Asia is one of the Indonesia national flight company which is using Airbus 320-200 and Boeing 737 – 300 for route Jakarta – Yogyakarta – Jakarta. The problem of the research is the high frequency of the flight based on the number of passengers on that route. Using two methods; field and library research and analyzed by market share analysis, linear trend, seat load factor (SFL), to find out the needs of flight frequency, the number of passengers, and diagram rotation. The result shows that there is an addition to the number of passengers and flight frequency of the route. Based on the analysis, Y = a+bX, the fluctuation trend pax on the first quarter route Jakarta – Yogyakarta is 68 % and on the second quarter route Yogyakarta – Jakarta is 67 %. For SFL, route Jakarta – Yogyakarta in the third quarter is 86 % dan the opposite route is 80 %.